Estate planning basics : what you need to know about wills, trusts & avoiding probate - Clifford, Denis (Nolo, 2026)
"This book explains the basics of estate planning concisely and clearly. It's the core of estate planning, made interesting! No fluff, just the key information about wills, trusts, planning for retirement, health care directives, estate taxes, and more." --